1997
DOI: 10.1111/1467-8721.ep11512617
|View full text |Cite
|
Sign up to set email alerts
|

Bilingual Memory and Hierarchical Models

Abstract: Do bilinguals represent their two languages in one or two memory stores? Consider a word such as loz'e. This word elicits certain associations pertaining to relationships or emotions involving objects, things, or persons, especially for a monolingual speaker of English. Now, consider tliis same concept in a bilingual setting. Docs the concept of "love" carry information regarding its translation equivalent of aruor (e.g., the fact that in Spanish this concept is used primarily to show emotions to persons, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 15 publications
7
53
0
2
Order By: Relevance
“…For instance, previous studies have shown that language dominance accounts for phonological transfer in production (Amengual, 2011(Amengual, , 2013(Amengual, , 2014(Amengual, , 2015Bullock et al, 2006;Simonet, 2011Simonet, , 2014, perception (Antoniou et al, 2012;Bosch et al, 2000;Pallier et al, 1997;Sebastián-Gallés and Soto-Faraco, 1999) and lexical storage (Amengual, in press;Pallier et al, 2001). Additionally, it has been found to influence code-switching patterns (Basnight-Brown and Altarriba, 2007), govern bilingual lexical memory representation (Heredia, 1997), affect language choice for self-directed and silent speech (Dewaele, 2004) and determine the language of mental calculations (Tamamaki, 1993).…”
Section: Language Dominancementioning
confidence: 99%
“…For instance, previous studies have shown that language dominance accounts for phonological transfer in production (Amengual, 2011(Amengual, , 2013(Amengual, , 2014(Amengual, , 2015Bullock et al, 2006;Simonet, 2011Simonet, , 2014, perception (Antoniou et al, 2012;Bosch et al, 2000;Pallier et al, 1997;Sebastián-Gallés and Soto-Faraco, 1999) and lexical storage (Amengual, in press;Pallier et al, 2001). Additionally, it has been found to influence code-switching patterns (Basnight-Brown and Altarriba, 2007), govern bilingual lexical memory representation (Heredia, 1997), affect language choice for self-directed and silent speech (Dewaele, 2004) and determine the language of mental calculations (Tamamaki, 1993).…”
Section: Language Dominancementioning
confidence: 99%
“…The inclusion of this group enabled us to examine the speed and accuracy of L1 processing when the native language has ceased to dominate. Heredia (1997) has noted that a shortcoming of the revised hierarchical model is that it tends to emphasize the development of links between representational systems during acquisition, neglecting potential changes that may occur after a reasonably high level of proficiency in L2 has been achieved. The strength of the mappings between representations are likely to vary with the relative dominance of L1 and L2, such that L1 mappings may weaken as L2 becomes the primary language.…”
Section: L2 Acquisition and Attritionmentioning
confidence: 99%
“…The view that emerged from early research (Potter, 1979) and is still favored (Heredia, 1997;Schreuder & Weltens, 1993) is that the two languages are represented at the lexical level in separate memory stores but have a common amodal conceptual store. But the way in which these stores are related has continued to be a matter of debate.…”
mentioning
confidence: 99%